2020
DOI: 10.1101/2020.03.10.985317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complete genome sequence and analysis of nine Egyptian females with clinical information from different geographic regions in Egypt

Abstract: Egyptians are at a crossroad between Africa and Eurasia, providing useful genomic resources for analyzing both genetic and environmental factors for future personalized medicine. Two personal Egyptian whole genomes have been published previously and here nine female whole genome sequences with clinical information have been added to expand the genomic resource of Egyptian personal genomes. Here we report the analysis of whole genomes of nine Egyptian females from different regions using Illumina short-read seq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Previous studies indicated that Egyptians are highly admixed, with substantial ancestry arising from the Middle East, Europe, and Africa-with the extent of European and Caucasus hunter-gatherer (Lazaridis et al, 2016) contribution being higher, and the African contribution being lower, than might be expected from geography. Greater European/Middle Eastern than African ancestry is also supported by wholegenome sequencing (ElHefnawi et al, 2021). Importantly, modern Egyptians are quite divergent from ancient populations.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies indicated that Egyptians are highly admixed, with substantial ancestry arising from the Middle East, Europe, and Africa-with the extent of European and Caucasus hunter-gatherer (Lazaridis et al, 2016) contribution being higher, and the African contribution being lower, than might be expected from geography. Greater European/Middle Eastern than African ancestry is also supported by wholegenome sequencing (ElHefnawi et al, 2021). Importantly, modern Egyptians are quite divergent from ancient populations.…”
Section: Discussionmentioning
confidence: 84%